Reconstruction of the late Holocene paleoenvironment of the western Beagle Channel (Argentina) based on a palynological analysis - Candel, Maria Soledad (2017)
Palynological analysis was performed on sediment samples from Arroyo Baliza site (54° 51′ S, 68° 33′ W), western sector of the Beagle Channel, Tierra del Fuego, Argentina, in order to reconstruct the palaeoenvironmental history during the Holocene marine transgressive-regressive cycle in the Beagle Channel. The palynological analysis reveals the presence of a closed-canopy Nothofagus forest development in the coastal areas under a cold, wet and variable climate conditions during the late Holocene. The marine assemblage composition shows similarities to those modern assemblages recorded in the surface samples from the Beagle Channel, characterised by the dominance of Peridiniales taxa, suggesting environmental conditions during the late Holocene comparable to today. The increasing salinity during middle Holocene was accompanied by an increase in number and diversity of the microplanktonic assemblages, suggesting the gradual installation of a marine environment as it exists today in the Beagle Channel.